Lipo-chitooligosaccharide and thuricin 17 act as plant growth promoters and alleviate drought stress in Arabidopsis thaliana - Subramanian, Sowmyalakshmi; Mitkus, Erika; Souleimanov, Alfred; Smith, Donald L. (Frontiers in Microbiology, 2023)
Lipo-chito-oligosaccharide (LCO -from Bradyrhizobium japonicum) and thuricin 17 (Th17 -from Bacillus thuringiensis) are bacterial signal compounds from the rhizosphere of soybean that have been shown to enhance plant growth promotion in various legumes and non-legumes. In this study, an attempt to quantify phytohormones involved in the initial hours after exposure of Arabidopsis thaliana to these compounds was conducted using UPLC-ESI-MS/MS. At 24 h post exposure to the signal compounds under optimal growth conditions, Arabidopsis thaliana rosettes varied in their responses to the two signals. While LCO treated rosettes showed a decrease in total IAA, cytokinins, gibberellins and jasmonic acid, an increase in ABA and SA was very clear. Th17 treated rosettes, on the other hand, showed an increase in IAA and SA. Both treatments resulted in decreased JA levels. A petri-plate assay, to screen for drought tolerance to PEG 8000 infusion, was conducted and plant growth studied 21 days post stress. Under severe drought stress, treatments LCO and Th17 were found to significantly increase fresh and dry weight over drought-stressed control plates, indicating that the presence of the signaling compounds decreased the negative effects experienced by the plants. Arabidopsis thaliana plants grown in trays with drought stress imposed by water withhold were used for free proline, elemental analysis and untargeted proteomics using LC-MS/MS studies. Free proline content increased in LCO and Th17 treated plants after drought stress. Elemental analysis showed a significant increase in carbon percentage at the lower concentration of Th17. Untargeted proteomics revealed changes in the levels of drought specific ribosomal proteins, glutathione S-transferase, late embryogenesis proteins, vegetative storage proteins 1 and 2, thaumatin-like proteins and those related to chloroplast and carbon metabolism. The roles of some of these significantly affected proteins detected under drought stress are discussed.